Dissecting the genetic variation of haploid frailty in maize for enhanced doubled haploid breeding - Fakude, Mercy; Murithi, Ann; Chen, Yu-Ru; Yavuz, Recep; Aboobucker, Siddique Imran; Frei, Ursula Karoline; Lübberstedt, Thomas (Frontiers in Plant Science, 2025)
Haploid frailty (HF), the reduced vigour of haploids compared to their diploid counterparts, limits the efficiency of doubled haploid (DH) breeding in maize. This study evaluated 192 BS39 perfect isogenic haploid–diploid pairs across two replications to quantify HF in eight agronomic traits and integrate analyses of HF with haploid fertility, genomic prediction, and genome-wide association studies (GWAS). Haploids were on average 30–40% shorter in plant and ear height, while traits such as tassel branch number showed minimal or even negative frailty, indicating the presence of naturally vigorous haploids. Heritability was consistently high for diploid (0.8–0.9) and haploid performance (0.7–0.9), but lower for HF (0.1–0.7), reflecting its complexity as a derived trait. Correlation analyses revealed strong diploid–haploid relationships (r = 0.5–0.9) and moderate negative associations between haploid performance and HF (r = –0.4 to –0.6). Importantly, haploid female fertility correlated positively with vigour traits, suggesting that dual improvement of vigour and fertility is possible. Genomic prediction using diploid data showed moderate accuracy for haploid traits (0.3–0.5) but weak performance for HF, showing the need for direct haploid evaluations. GWAS detected significant SNPs across traits, including 14 for plant height, 30 for ear height, 20 for flag leaf length, 19 for flag leaf width, 23 for tassel length, 2 for spike length, and 6 for tassel branches, with one SNP shared between haploid and diploid tassel branches. Candidate genes included regulators of cell cycle control (Myb3R-1), auxin signalling (SRS1, SAUR-like proteins), cytoskeletal organization (PRONE-domain proteins), and oxidative stress protection (HGGT1).